Saint Vincent and the Grenadines. Significant achievements 2011 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2022)
The main activities carried out by the Institute in Saint Vincent and the Grenadines during 2011 are identified, with respect to the needs and interests of the country, strengthening topics such as sustainability, nutrition, production, poultry, beekeeping, leadership, organizational management, good practices. of manufacturing, companies, profitability, technical cooperation, inclusion of women and chicken production.